Obtenção e caracterização de filmes à base de blendas de fécula de batata, quitosana e alginato de sódio - Gonçalves, Francielle Cristine Pereira (2021)
Diverse studies are being carried out from an ecological basis, aiming not only at a good performance of the material, but also at a positive alternative when it comes to sustainability. The distinction of sustainable development has gained vital importance, especially due to the shortage of raw materials derived from non-renewable natural resources and the problems resulting from environmental degradation. The search for products derived from sustainable materials has been treated as a basic tool in the search for alternatives to minimize the world's environmental problems. The use of raw materials from renewable sources has been an object of studies and research by several institutions, due to its potential to substitute products derived from petroleum. Based on this statement, the objective of this study was to obtain and characterize biodegradable films composed of ternary blends of biopolymers. The films produced were composed of chitosan, potato starch and sodium alginate, based on an experimental planning employing ternary mixture plan. The filmogenic solutions were obtained by the casting technique, with the dry matter fixed at 2%. The plasticizer used was glycerol and its percentage was fixed at 20%, in relation to the dry mass of biopolymer. After the production of biofilms, these were cut into specimens, to perform the mechanical characterization, SEM, solubility, PVA, color and opacity. An analysis of variance (ANOVA) was performed to obtain the models and the F Test was used to verify their statistical significance. After this verification, the graphs of response surfaces were generated. From the surfaces and the models obtained it was possible to evaluate the effect of the composition of the biopolymer blends on the parameters of tensile strength limit, modulus of elasticity, elongation at break, solubility, and water vapor permeability. The surface morphologies of the films were analyzed using the obtained micrographs (SEM) and used in understanding the properties of the films. The results pointed out that the polymeric blend of test 13 (80% potato starch and 20% sodium alginate) has the highest tensile strength, around 90% higher than potato starch alone, 71% higher than alginate alone, and 79% higher than chitosan alone. Regarding Young's modulus, it was observed that the blend of test 11 (80% potato starch and 20% chitosan) presented the highest modulus, around 90% higher than starch alone, 85% higher than chitosan alone, and 69% higher than alginate. The elongation at rupture, on the other hand, was greater with the blend of test 12 (80% chitosan and 20% alginate), around 86% greater than starch, 55% greater than chitosan and 82.8% greater than alginate. The concentration of chitosan in the formulation of the films negatively influenced the solubility property, compared to the blend that showed the lowest solubility rate, test 13 (80% potato starch and 20% sodium alginate), the chitosan is about 15% less soluble and this occurs due to the presence of free amino groups, being thus insoluble in water. The films that contained the presence of potato starch obtained better barrier properties, compared to the blend that showed the lowest rate of water vapor permeability, test 15 (80% chitosan and 20% potato starch), this showed to be about 15% less permeable. From the surface morphology analyzed it was observed the homogeneous and compact formation of biofilms. The biofilms constituted by the combination of two or more biopolymers showed satisfactory properties when compared to biofilms formulated by a single component